Annotation Query (AnnoQ): an integrated and interactive platform for large-scale genetic variant annotation. Issue Volume 50:Issue W1(2022) (30th May 2022) - Liu, Zhu; Mushayahama, Tremayne; Queme, Bryan; Ebert, Dustin; Muruganujan, Anushya; Mills, Caitlin; Thomas, Paul D; Mi, Huaiyu
Abstract: The Annotation Query (AnnoQ) (http://annoq.org/ ) is designed to provide comprehensive and up-to-date functional annotations for human genetic variants. The system is supported by an annotation database with ∼39 million human variants from the Haplotype Reference Consortium (HRC) pre-annotated with sequence feature annotations by WGSA and functional annotations to Gene Ontology (GO) and pathways in PANTHER. The database operates on an optimized Elasticsearch framework to support real-time complex searches. This implementation enables users to annotate data with the most up-to-date functional annotations via simple queries instead of setting up individual tools. A web interface allows users to interactively browse the annotations, annotate variants and search variant data. Its easy-to-use interface and search capabilities are well-suited for scientists with fewer bioinformatics skills such as bench scientists and statisticians. AnnoQ also has an API for users to access and annotate the data programmatically. Packages for programming languages, such as the R package, are available for users to embed the annotation queries in their scripts. AnnoQ serves researchers with a wide range of backgrounds and research interests as an integrated annotation platform. Graphical Abstract: